HUBUNGAN ANTARA KARAKTERISTIK PEKERJAAN IBU DENGAN STATUS GIZI ANAK USIA 4-6 TAHUN DI TK SALOMO PONTIANAK - ., Devi Kristianti (ProNers, 2013)
Abstract Children aged 4-6 years old are the most vulnerable groups experiencing nutritional problems which are in a period ofgrowth and development and for the establishment of future physical, psychological, and their intelegance. Nutritionalproblems may be influenced by maternal factors such as maternal employment, maternal education, or maternalknowledge. This study aims to determine the relationship between the nutritional status of children aged 4-6 years withmaternal employment. This research is quantitative research using survey methods with a cross-sectional approach.Subjects in this study were 40 mothers and children aged 4-6 years in Salomo Kindergarden Pontianak taken withconcecutive sampling. Information about mother’s characteristics was collected using a questionnaire and thenutritional status of children was collected by measuring their anthropometric measurements. The data was analyzedusing Chi Square Test with a 95% significance level. Most respondents were mothers that were 35 years old above(57.5%), employed (52.5%), having higher education (50%), and a good knowledge about nutrition (82.5%).Nutritional status of children mostly good/normal (80%). Chi square test results showed there was no correlationbetween mother’s employment with the child's nutritional status (p = 0.805), there was no correlation of mother’seducation with the children's nutritional status (p = 0.595), and the mother’s knowledge was correlated with nutritionalstatus of children (p = 0.046). It can be concluded that mothers' knowledge on nutrition can affect the nutritional statusof children. The suggestion of this research was mothers can inmproved the nutritional needs of the children inaccordance with a nutrition balance guidelines because founded children with obesity in this study. Keywords: Nutritional Status, Children Aged 4-6 Years Old, Mother's Employment